The Maternal Referral Profile Before and During the Covid-19 Pandemic at the Educational Hospital and Affiliation Hospital in Makassar City 2019 - 2021 - Andi Muldiani Dwi Rachmayana; Abdul Rahman; Elizabet C Jusuf (Faculty of Medicine, Hasanuddin University., 2022)
Background: The Covid-19 pandemic is a global outbreak. Several nations, including Indonesia, have implemented COVID-19 infection prevention and control measures. The biggest concern is for disadvantaged populations at higher risk, one of which is pregnant women. Several aspects of health services, including maternal health care facilities, saw adjustments during this restriction period. Pregnant women are apprehensive about visiting the Community Health Center for fear of contracting an infection. As a result, maternal and newborn health services, including access to and quality of maternal and referral services, become affected. Method: it was a descriptive retrospective method within 3 years data. Data were collected from registration data of obstetric referral cases at Education Hospital and Affiliated Hospital in Makassar City. Results: Between before and during the COVID-19 pandemic, the number of maternal referral cases decreased by half, which the highest variables are reproductive age, Grande Multipara, Insurance methods using the National Health Insurance, and according to the criteria of refferal is the potential for Obstetrics Emergency. Conclusion: There was a decline in maternal referral cases in Education Network hospitals before and during the COVID-19 pandemic.